Physical Test of Sinking Feed Made from Fermented Fish Filet Waste Meal - Nur Fauzy, Fahmy; Andriani, Yuli; Iskandar, Iskandar; Meyllianawaty, Fittrie; Dwi Cahya, Muhammad (Torani Journal of Fisheries and Marine Science, 2024)
Fish feed is an important factor in aquaculture, where the physical properties of sinking feed affect its efficient use by fish. Waste fish filets have potential as an alternative feed, but farmers have difficulty finding high-quality feed at affordable prices. This study aims to determine the physical properties of feed with the addition of fermented fish filet waste flour (TLFIF). The method used was a completely randomized design (CRD) with 5 treatments and 3 replicates: P0 (control, without TLFIF), P1 (10% TLFIF), P2 (20% TLFIF), P3 (30% TLFIF), and P4 (40% TLFIF). Parameters observed included: appearance test, aroma, texture, durability test, homogeneity test, and feed sinking speed test. Data were analyzed using analysis of variance (ANOVA) and descriptive analysis. The best TLFIF addition research results were found in the 10% treatment (P1), which had a durability of 98.80%, homogeneity of 42.67%, and a sinking speed of 7.15 seconds/20 cm. The feed's appearance is light brown in color, cylindrical in shape, and fairly uniform in size, with a dense, fibrous texture, a slightly rough surface, and a slight fermentation aroma.